The value of traditional milk products among smallholder farmers of Southern Ethiopia: handling, consumption and making of butter - Tsedey Azeze; Mitiku Eshetu; Zelalem Yilma; Tesfemariam Berhe (Cogent Food & Agriculture)
Although earlier studies reported on traditional dairying, there is limited information on variation in milk and milk products handling, production, and consumption across various dairy production systems (DPS) in Southern Ethiopia, which is why this study was initiated. This study assessed 360 smallholder dairy producer households across four DPSs in the Sidama and the former Southern Nations, Nationalities, and People’s (SNNP) Regional States of Ethiopia: cereal-based (CB) diversified crop-based (DCB), Ensete-based (EB), and cash crop-based (CCB). Over two-thirds of respondents in CCB use improved milk handling devices like aluminum cans and Mazzicans, compared to 21% in EB. Eucalyptus globulus were primarily used to clean milk equipment in the CB, DCB and EB DPSs, whereas enset plant residue (‘kacha’ in Amharic) was specific to CCB. Olea africana was commonly used to smock milk containers across all systems. More milk (18 liters) was required to produce one kg of butter from crossbred cows, while local breeds required 13 liters on average. In the CB system, crossbred cows needed a minimum of 15 liters of milk to produce one kg of butter. Higher annual milk production per household was reported in the CCB, with the lowest in the DCB. Whole milk consumption did not significantly vary among the DPSs (P < 0.05). On average, 38% of the produced milk was processed into traditional butter, with the lowest proportion (27%) in CCB and the highest (42%) in DCB. These findings suggest the need for tailored development options in milk handling, processing and butter making along with the introduction and adoption of improved handling technologies for the different DPSs in Southern Ethiopia.